“Kutipan Ayat” Dan Kehadiran Alquran: Meninjau Konstruksi Imam Nawawi Atas Adab Menghormati Mushaf Dan Tulisan Alquran Dalam Al-Tibyan Fi Adabi Hamlat Al-Qur’an - Muhammad Saifullah (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
This essay is going to depict how Imam Nawawi’s construction upon courtesy in deal with something containing Qur’an verses within al-Tibya>n. Imam Nawawi had brought out particular issue in which foregoing works such al-Muhazz^ab and Niha>yat al-Mat}lab did not issue. For instance, regarding the case in 11 century Imam Shirazi did not point out anything not to touch when one is in h}adas^ (ritual impurity) except fikih, whereas a century after Imam Juwaini issued a book of h}awa>sy and ust}u>rah, and subsequently in 13 Imam Nawawi come with new additional outlook of book which muh}dis^ (one who has h}adas^) could not touch: tafsi>r and h}adis^. By borrowing Klaus Krippendor’s content analysis and a pattern of transmission-transformation, the essay interests to investigate why a shift-mentioned is able to come up, how can it be happened, and in what extent it had been transmitted. The article therefore argues that the shift within modesty of treating Qur’an verses is triggered by a couple things: context differences surround each Imam and their peculiarly effective history—to use Gadamer’s phrase. Afterward, concerning form, though an appropriation is intensively occurring, a static point can be constantly found which is always approached to be maintained.